2017
DOI: 10.1016/j.worlddev.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Welfare Effects of Nigeria's e-Voucher-Based Input Subsidy Program

Abstract: HighlightsThe productivity and welfare effects of an e-voucher subsidy program are evaluated.Instrumental variable regression employed to control for endogeneity.The program is effective in improving productivity and welfare outcomes.No heterogeneity effects based on gender and farm land size.The program has a modest benefit–cost ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
83
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 24 publications
(47 reference statements)
11
83
0
4
Order By: Relevance
“…Farmers also developed more capacity on maize farming with a percentage of 35.5% (70) of total respondents. This supports the view of Wossen, et al, (2017) that agricultural projects targeted to reduce rural poverty and to increase food security could improve productivity and welfare outcomes of beneficiary smallholder farmers.…”
Section: Impact Of Red Hub Project On Maize Farmers Incomesupporting
confidence: 76%
See 1 more Smart Citation
“…Farmers also developed more capacity on maize farming with a percentage of 35.5% (70) of total respondents. This supports the view of Wossen, et al, (2017) that agricultural projects targeted to reduce rural poverty and to increase food security could improve productivity and welfare outcomes of beneficiary smallholder farmers.…”
Section: Impact Of Red Hub Project On Maize Farmers Incomesupporting
confidence: 76%
“…It is the view of Tagne, et al, (2008);Mokhel, et al, (2016);Melusi, et al, (2016) that maize is the foremost income earner to farmers to most developing countries with poor resources. Similarly, Wossen, et al, (2017) observed that agricultural projects targeted to reduce rural poverty and to increase food security could improve productivity and welfare outcomes of beneficiary smallholder farmers. Eastern Cape Provincial government in their effort to encourage commercial production of maize, processing and marketing targeted at increasing maize farmers' income and food security in the study area introduced the Rural Enterprise Development Hub Project model in partnership with the Development Bank of Southern Africa and ECRDA, 20132014/15;and 2015/16 Annual Reports).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evaluations of the impact of fertilizer subsidies on fertilizer application and associated inputs remain inconclusive, and the impacts may differ by context. Several studies show that fertilizer subsidy programs have increased fertilizer use intensity (Chibwana et al 2014;Mason and Jayne 2013) and productivity (Dorward and Chirwa 2011;Liverpool-Tasie and Takeshima 2013;Lunduka, Ricker-Gilbert, and Fisher 2013;Mason and Jayne 2013;Wossen et al 2017). On the other hand, other studies show that fertilizer subsidies crowd-out commercial fertilizer use and hamper the development of the commercial fertilizer sector (Mason and Jayne 2013;Ricker-Gilbert, Jayne, and Chirwa 2011;Xu et al 2009;Takeshima and Nkonya 2014; Ricker-Gilbert and Jayne 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The e‐wallet system technology ensures that a Nigerian farmer receives farm input subsidy support from the FGN through accredited agro‐dealers, provides vital agro‐information alerts, is available to the agricultural extension system, and facilitates microlending and insurance schemes (Olomola, ). The rapid adoption of the e‐wallet program has generated a great deal of speculation and optimism regarding its effect on economic development in the country (Adenagan, Fagbemi, Osanyinlusi, & Omotayo, ; Adesina, ; Grossman & Tarazi, ; Uduji & Okolo‐Obasi, ; Wossen et al, ). However, an emerging body of research shows that the reduction in communication costs associated with the e‐wallet program has intangible economic benefits, including the improvement of agricultural and labor market efficiency as well as producer and consumer welfare in specific circumstances and areas (Adebo, ; Fadairo, Olutegbe, & Tijani, ; Nwalieji, Uzoegbunam, & Okeke, ; Tiri, Ojoko, & Aruwayo, ).…”
Section: Introductionmentioning
confidence: 99%